Small is beautiful but not trendy: Understanding the allure of big hydraulic works in the Euphrates-Tigris and Nile waterscapes - Hussein, Hussam; Conker, Ahmet; Grandi, Mattia (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The number of massive hydraulic infrastructures such as large-scale dams, huge hydropower plants, and broad irrigation networks has increased to an unprecedented level during the twentieth century. While the trend has recently slowed, building giant water infrastructures is still an utmost priority in many parts of the world across state elites. Informed by insights from major transboundary waterscapes - the river basins of the Euphrates-Tigris and the Nile - this paper analyses how states ' elites justify their hydraulic mission, finding that four distinctive discursive practices are efficiently used in the case studies: securitization, opportunization, de-politicization, and framing.
Keywords: Middle East and North Africa; hydraulic infrastructures; water policy; hydraulic mission; hydropolitics; ANATOLIA PROJECT GAP; WATER; DAMS; CONFLICT; POLITICS; ETHIOPIA; ROGUN; POWER; WAR; Area Studies; International Relations; Government & Law